Aquatic Oligochaete Biology VIII 2001
DOI: 10.1007/978-94-010-0597-5_4
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of oligochaetes in Poyang Lake, the largest freshwater lake of China, and its vicinity, with description of a new species of Limnodrilus

Abstract: The oligochaete fauna of the largest freshwater lake of China, Poyang Lake, has never been investigated before. On the basis of a preliminary survey in the lake and its vicinity in 1997-1999, 25 species belonging to 20 genera and 5 families are recorded. Among them, one genus, Cernosvitoviella (Enchytraeidae), and two species, Bratislavia unidentata (Naididae), Potamothrix bedoti (Tubificidae), are recorded from China for the first time. Another tubificid, Limnodrilus paramblysetus sp. nov., is new to science.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 12 publications
(12 reference statements)
1
16
1
Order By: Relevance
“…Combining our results with other reports (Lin 1962;Tchang and Li 1965;Liu and Wu 1991;YG Chen 1988;XP Wu et al 1994, 2000Wang et al 1999;Gibson and Wang 2002), nearly 130 zoobenthic species have been described there. In comparison with other Chinese lakes (QY Chen et al 1980;YY Chen et al 1995;Liang and Liu 1995), Poyang Lake has the highest richness of macroinvertebrates.…”
Section: Ecological Role Of Benthos In Poyang Lakesupporting
confidence: 88%
See 1 more Smart Citation
“…Combining our results with other reports (Lin 1962;Tchang and Li 1965;Liu and Wu 1991;YG Chen 1988;XP Wu et al 1994, 2000Wang et al 1999;Gibson and Wang 2002), nearly 130 zoobenthic species have been described there. In comparison with other Chinese lakes (QY Chen et al 1980;YY Chen et al 1995;Liang and Liu 1995), Poyang Lake has the highest richness of macroinvertebrates.…”
Section: Ecological Role Of Benthos In Poyang Lakesupporting
confidence: 88%
“…To date, only some faunistic fi ndings have been reported JH Wu et al 2000;Wang and Liang 2001;Gibson and Wang 2002). In this article, we present an overview of the zoobenthic community, mainly the aspects of standing crop and functional feeding groups.…”
Section: Introductionmentioning
confidence: 95%
“…These studies showed that there are 108 species of Mollusca in Lake Poyang, of which more than 50% are Chinese endemic species. In contrast, few studies have been conducted on other taxonomic groups (e.g., Annelida and aquatic insects) (Xie et al, 1995, Wang et al, 1999Ou Yang et al, 2009;Pan et al, 2011). Furthermore, rare researches have been implemented on the factors regulating the community structure of macrozoobenthos (Pan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This is the second species of Potamothrix recorded from China. The first, P. bedoti (Piguet, 1913), was reported from a shallow lake in Wuhan by Wang and Liang (2001).…”
Section: Disscusionmentioning
confidence: 99%
“…Previous studies of freshwater oligochaetes in China have mainly been conducted in the east, whence 28 species and 14 genera of Tubificidae have been recorded so far (Chen, 1940;Liang, 1962, 1979, Erséus and Qi, 1985Brinkhurst et al ., 1990;Liang and Xie, 1997;Wang and Liang, 2001;Wang, 2002). Few taxa were hitherto known from the west.…”
Section: Introductionmentioning
confidence: 99%